Capacity-increasing robust porous SiO2/Si/graphene/C microspheres as an anode for Li-ion batteries. Issue 51 (9th May 2016) - Wang, Jiande; Chen, Xiaohua; Liu, Xuelian; Hu, Aiping; Tang, Qunli; Liu, Zheng; Fan, Binbin; Chen, Huaiyuan; Chen, Yuxi
Abstract : We unprecedentedly studied the synergetic effects between SiO2 and Si as an anode for lithium-ion batteries, and the prepared composite exerts an increasing capacity. Abstract : Robust porous SiO2 /Si/graphene/C microspheres have been successfully synthesized by a simple two-step process of ultrasonic spraying and partial magnesiothermic reduction. The 3-D porous microspheres consist of Si/SiO2 nanoparticles (around 5–10 nm) covered by a layer of carbon and connected by graphene. We explored the electrochemical properties of the porous microspheres as an anode for lithium ion batteries (LIBs). In SiO2 /Si/graphene/C microspheres, numerous pores could leave enough room for volume expansion and contraction of silicon during lithiation and delithiation, and provide large space voids for electrolyte reserves. Meanwhile, graphene plays a role in reinforcing the porous structure. The prepared sample shows superior cyclability with a discharge capacity of 1104.9 mA h g −1 in the second cycle and 1141.6 mA h g −1 over 200 cycles at a current density of 0.1 mA cm −2 . The capacity retention is more than 100%, making it very promising as a future LIBs anode.